Diversity and conservation of legumes in the Gran Chaco and biogeograpical inferences - Morales, Matias; Oakley, Luis; Bagnatori Sartori, Angela Lucia B.; Mogni, Virginia Y.; Atahuachi, Margoth; Vanni, Ricardo O.; Fortunato, Renee Hersilia; Prado, Darién E. (Plos ONE, 2019)
The Gran Chaco is a wide ecologic-geographic region comprising northern Argentina, western Paraguay, southern Bolivia and the southwestern extreme of Brazil. This region exhibits extreme temperatures, annually regular frosts, and sedimentary soils; it has been dramatically threatened by agriculture expansion in recent decades. Therefore, increasing knowledge of plant diversity is critical for conservation purposes. We present a Legume checklist of the Gran Chaco ecoregion including conservation status of its endemic species. Leguminosae is the third most diverse plant family in the Neotropics. Assuming a rigorous spatial definition of the Gran Chaco, we recorded 98 genera, 362 species, and 404 specific and infraspecific taxa. Endemic/typical taxa were 17%, comparable to adjacent tropical plant formations, and they were found in higher percentages in Caesalpinioideae (24%) and Cercidoideae (33%) than Papilionoideae (11%) subfamily. We also analyzed the plant diversity comparing lineages and subregions. The Gran Chaco Legumes are predominantly widespread generalists, or they belong to either Chaco sensu stricto or Neotropical Seasonally Dry Tropical Forest (SDTF) lineages. Though the Humid Chaco registered the highest species richness, Dry Chaco and Sierra Chaco, the most threatrened subregions, exhibited the highest percentages of exclusive and proper Chaco-lineage species. These results suggest that diversification of Legumes has been most relevant in Dry Chaco and Sierra Chaco, probably by their more demanding and harsh environmental conditions limiting the dispersion of generalists or intrusive-invading species. This study is paramount to reach an improved delimitation of the Gran Chaco ecoregion in transitional areas with the SDTF and Cerrado formations. Conservation status is critical in genera of high economic interest, such as Arachis, Mimosa and Prosopis. At least one third of endemic taxa exhibit a critical status of conservation or are endangered, many of them being relevant to inbreeding program or exhibiting multiple economic uses.